Emma on thin icing - Simon, Coco. (New York : Simon Spotlight, 2011)
Mia asks the girls in the Cupcake Club to be junior bridesmaids in her mother's wedding.
Keywords: Friendship -- Fiction; Clubs -- Fiction; Cupcakes -- Fiction; Moneymaking projects -- Fiction; Weddings -- Fiction